2021
DOI: 10.2174/1573405617666210218100641
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Framework for the Detection of Intracranial Hemorrhage in CT Brain Images Using Deep Learning

Abstract: Background: The need for accurate and timely detection of Intracranial hemorrhage (ICH) is utmost important to avoid untoward incidents that may even lead to death.Hence, this presented work leverages the ability of a pretrained deep convolutional neural network (CNN) for the detection of ICH in computed tomography (CT) brain images. Methods: Different frameworks have been analyzed for their effectiveness for the classification of CT brain images into hemorrhage or non-hemorrhage conditions. All these frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The discrepancy rate between primary RR and AI analysis was 3.3%. Working with AI holds opportunities and challenges for both radiologist and skillful clinicians who, in addition to maintaining their expertise also need to be aware of the pitfalls of the specific software solutions [ 43 , 44 ]. Specifically, both radiologists and clinicians can and should consult a patient’s past and current medical history, previous imaging data, and additional CT reconstructions to form a comprehensive diagnosis where results appear inconclusive ( Fig 5 and S5 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy rate between primary RR and AI analysis was 3.3%. Working with AI holds opportunities and challenges for both radiologist and skillful clinicians who, in addition to maintaining their expertise also need to be aware of the pitfalls of the specific software solutions [ 43 , 44 ]. Specifically, both radiologists and clinicians can and should consult a patient’s past and current medical history, previous imaging data, and additional CT reconstructions to form a comprehensive diagnosis where results appear inconclusive ( Fig 5 and S5 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…The data sources analysis was divided into single [ 20 , 22 , 24 , 26 , 27 , 30 , 32 34 , 36 39 , 41 , 42 , 47 , 48 , 50 ] or multiple [ 21 , 23 25 , 27 , 28 , 31 , 34 , 35 , 43 , 45 49 ]. These results were not significant for the sensitivity (p-value = 0.6879), specificity (p-value = 0.6494), and DOR (p-value = 0.7272) ( Additional file 1 : Figures S9–S11).…”
Section: Resultsmentioning
confidence: 99%
“…Detection of ICH by ML in systematic studies may decrease the time to diagnosis, which is crucial for clinical because approximately most of ICH in accordance with death occurs within the primary hours [ 53 ]. This meta-analysis demonstrated that ResNet algorithms could detect ICHs accurately with retrospective and non-randomized data [ 22 , 31 , 33 , 37 , 38 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study performed by Kumaravel et al , using the CQ500 open data set, the hemorrhage types were evaluated in general, and the presence or absence of hemorrhages was examined. [ 45 ] AlexNet, an old deep learning model, was used and a success rate of around 99% was achieved. [ 45 ] This shows that the images in the dataset are not very complex in terms of classification.…”
Section: Discussionmentioning
confidence: 99%